Indexing innovation within China. Issue 4 (15th July 2019) - Reid, David McHardy; Chi, Guotai; Zhao, Zhi Chong; Alon, Ilan
Abstract : Purpose: Performed over a five-year time horizon, this paper aims to analyze the progression rates of technological innovation across 15 sub-provincial Chinese cities. The authors quantify and rate innovation performance, then rank the cities based on a purpose-built index designed to gauge the rate of technological progress. Design/methodology/approach: Using the inferior constraint method, and a variety of national sources of data, the authors construct an innovation index based in part on new product sales revenue, proportion of college students, research and development expenditure of industrial enterprises in relation to gross industrial output value, contract deals in technical markets per capita, hazard-free treatment rate of waste, enterprises with technical development agencies accounts for industrial enterprises, number of high-tech enterprises and invention patent ownership per million population. Findings: The findings provide a methodology for indexing cities, with 15 Chinese provincial cities as examples. Among the top five cities with the highest technological innovation index were Shenzhen, Nanjing, Guangzhou, Hangzhou and Wuhan. In the bottom were Shenyang, Changchun, Dalian, Xi'an and Harbin. Research limitations/implications: This study applied a new model of innovation at the city level for China. Application to other industries (real estate, manufacturing, etc.) and countries will extend boundaries of this model and show its wider applicability. Practical implications: Companies can use this research and methodology when seeking new investments in high tech and innovative products. Locations offering more hospitable environments should be prioritized ceteris paribus . Originality/value: One weakness of much of the international business and competitiveness literature is that it often views the country as the primary unit of analysis. In this way, nuanced views of the institutional environments within countries are often overlooked. This paper proposes a measure of regional rates of innovativeness across China.